Guru Honorer dalam Lingkaran Ketidakadilan - Gagan Aditya Fauzan (Journal on Education, 2021)
This study aims to examine the value of justice for honorary teachers in the world of work and highlight various policies and issues that have strengthened in recent years from an ethical, legal, and human rights perspective. The method in this study is a qualitative method by conducting a literature review. The basic paradigm adopted is Justice as Fairness proposed by John Rawls. Sources of data that are used as references are books, secondary data, observations, and legislation related to research issues with the main reference book being A Theory of Justice as the result of John Rawls's thinking. This research is expected to provide an overview of the reality experienced by honorary teachers in the world of work, provide moral support for the struggle of honorary teachers in Indonesia, and insert an ethical perspective on the problems of honorary teachers in Indonesia. Some of the findings in this study are that the Ministry of Education and Culture as the institution that oversees honorary teachers creates a condition of circumstances of justice where it is necessary to apply the principles of social justice to create social cooperation, as well as a fair distribution of primary values ​​so that it does not cause economic inequality and can fulfill life. worthy. Besides being ethically unfair, the legal perspective also shows that there are still many parts of the law that have not been reflected on honorary teachers as workers.